Growth and yield of rice plants (Oryza sativa) grown in soil media containing several doses of inorganic fertilizers and sprayed with lombok brown algae extracts. Issue 1 (December 2020) - Sunarpi, H; Nikmatullah, A; Sunarwidhi, A L; Sapitri, I; Ilhami, B T K; Widyastuti, S; Prasedya, E S
Abstract: The use of inorganic fertilizers in rice production system in Indonesia, increases to an excessive level of application, which was 300 kg urea, 100 kg TSP, and 100 kg KCl per hectare, respectively. This application increases cost of rice production, reduces soil fertility, and farmers income, and harm environment. This article reports the effect of Lombok brown algae extracts on growth and yield of rice plants grown in soil media containing several doses of inorganic fertilizers. Lombok brown algaes, such as Sargassum crassifolium, Sargassum cristaefolium, Sargassum aquifolium, and Turbinaria murayana, were collected in Lombok Indonesia coastal beach. Each liquid extract 10% of brown algae, was sprayed to rice plants grown in soil media containing 0, 50%, or 100% dose of inorganic fertilizers recomended by Indonesian ministry of agriculture. The result showed that effect Lombok brown algae liquid extracts on chlorophyll content in leaf, N, P, K content in tissue, growth, and yield of rice plants, depends on dose of inorganic fertilizer applied in soil media. Similar phenomena were also found in growth and yield parameters. An interesting result found in this experiment that there were no significant effect of brown algae liquid extract on chlorophyll content in leaf, N, P, K content in tissue, growth and yield of rice plants grown in media containing 50% and 100% inorganic fertilizers. This indicates that the application of inorganic fertilizers could be reduced to 50% when the rice plants were also sprayed with brown algae liquid extract to gain the same yield of these supplied with 100% inorganic fertilizers.